Prispevek Franca Grivca pri ovrednotenju sv. Cirila in Metoda - Škafar, Vinko (Edinost in dialog, 2013)
At the 1150th anniversary of St. Cyril and Methodius to Moravia (863-2013) and the 50th anniversary of Franc Grivec's death (1878-1963) the author presents Grivec's contribution to the evaluation of St. Cyril and Methodius under three aspects: 1. Life of St. Cyril and Methodius, 2. biographies on St. Cyril and Methodius and 3. Ancestral honours in theology of St. Cyril and Methodius. Grivec burrowed himself four times in the translation and commenting of Žitja Konstantina in Žitja Metodija: in Slovenian in the years 1936 and 1951, and in Latin in 1941 and 1960. His research was based on the comparison of the Church Slavic sources, which are also illuminated by Latin and more modest Greek documents. Grivec tackles lives as a writer, professor of Slavic studies, philologist, historian and theologian who has deepened particularly interesting questions of lives. With systematic deepening on the type of questions Grivec indicates the leading idea of the Cyril and Methodius theology, spirituality and apostolate. The result of Grivec's research is also the reader for liturgical reading (breviary) on the feast of St. Cyril and Methodius and quotation of the last issue of his lives in the circular letter of the Pope John Paul II. Of the Apostle of Slavs. By making Grivec's research of lives present in the liturgical reading and the papal circular letter, his work remains present at the global level. The success of his research also lies in the fact that in his last stages of life he managed to make a felicitous synthesis of the life of Slavic preachers of the gospel, which is represented by his work in German: Konstantin und Method, Lehrer der Slaven (1960) and in Slovenian Slovanska blagovestnika sv. Ciril in Metod (1963). At the end of his research path Grivec using Cyril's syntagma on the ancestral honours and searching for wealth points towards the original foundation of pure and noble humanity, human dignity and human rights proclaimed only in 1948. Grivec was very excited to discover and indicate the importance of ancestral honours in the theology of St. Cyril and said: "In the spirit of his leading idea he was actually overcome by deep awareness of the unity of all people in Christianity and humanity, equality of all human beings and peoples within the family of nations and especially in Christianity and before God."
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; Grivec, Franc, 1878-1963; svetniki; Christianity; krščanstvo; krščanska teologija